Preferência pela liquidez dos bancos públicos no ciclo de expans\~ao do crédito no Brasil: 2003-2010 - Victor Leonardo de Araujo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study aims to show that during the cycle of credit expansion occurred in the Brazilian economy between 2003 and 2010, public banks had acted with a degree of liquidity preference higher than that of private banks until the international financial crisis. The need to achieve economic and financial results by public banks have guided and restricted his actions over the whole period.
Keywords: G21; E44; 330; Kreditgeschäft; Liquiditätspräferenz; Brasilien